Pemanfaatan Tepung Daun Apu-apu (Pistia stratiotes) dalam Ransum Basal terhadap Organ Pencernaan Ayam Ras Pedaging - R. Sitompul; E. Erwan; E. Saleh (Jurnal Peternakan, 2020)
Water lettuce meal (Pistia stratiotes) is the weed that has potential as animal feed due to it contain high crude protein and energy metabolism. The aims of this study wasto determine the weight and length of digestive organs including proventriculus, ventriculus, small intestine in broiler chicken given of water lettuce meal (WLM) in ratios. The research design of this study was a completely randomized design (CRD) with five treatments and four replications. The treatments consisted of T0 (commercial feed without WLM), T1 (ration with 0% WLM), T2 (ration with 5% WLM), T3 (ration with 10% WLM) and T4 (ration with 15% WLM). The experimental animal used were broiler DOC until the age of 35 days old were kept in 20 cages and each cage consisted of 3 broiler chickens. The parameters measured were proventriculusweight, ventriculus weight, small intestine weight and length of the small intestine. The results showed that there was no significant effects among treatments on all parameters. The conclusions of the study that the use of indicate that WLM could be used as feed up to 15% in ration without affecting their the proventriculus weight, ventrikulus weight, small intestine weight and length small intestineinbroiler chickens.